ACTIVITIES OF VIETNAM TRADE UNIONS AT THE GRASSROOTS LEVEL - Chi, Dinh Van (American International Journal of Social Science Research, 2021)
In this study, the author focuses on clear viewpoints about Vietnam Trade Unions and grassroots Trade Unions organized in state agencies, political organizations, socio-political organizations, professional socio-political organizations, professional social organizations, establishments, enterprises, cooperatives, other organizations employing workers as prescribed by labor laws and regulations, foreign agencies, organizations, international organizations operating in the Vietnamese territory. The grassroots trade union is responsible for implementing the following tasks: propagating and mobilizing workers to improve their qualifications, skills, careers, and law observance; Protecting the legal and legitimate rights and interests of employees; Participating in state management, socio-economic management, inspection, examination and supervision of activities of state agencies, organizations, units and enterprises; developing membership; building strong grassroots trade unions and participating in Party building. From these above goals, the author uses scientific research methods such as analysis and synthesis, interpretation and inductive, abstracting and generalization, logic, and history, history, and comparison to come to the conclusion proposed to the work of the Vietnam Trade Union at the current grassroots level.